2004
DOI: 10.1002/humu.20015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel candidate gene,CASC2, in a region of common allelic loss at chromosome 10q26 in human endometrial cancer

Abstract: Allelic deletions, which are suggestive for the presence of tumor suppressor genes, represent a common event in endometrial cancer (EC). Previous loss-of-heterozygosity studies for human chromosome 10q identified a candidate deletion interval at 10q25-q26, which we further narrowed to a 160-kb region at 10q26, bounded by markers D10S1236 and WIAF3299. Using a positional candidate approach, we identified three alternative transcripts of a novel human gene, CASC2 (cancer susceptibility candidate 2; formely C10or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 23 publications
2
75
0
Order By: Relevance
“…[24][25][26][27] However, the expression and functional role of CASC2 in the development of osteosarcoma are still uncovered.…”
mentioning
confidence: 99%
“…[24][25][26][27] However, the expression and functional role of CASC2 in the development of osteosarcoma are still uncovered.…”
mentioning
confidence: 99%
“…LncRNA CASC2 was first discovered in 2004 by Baldinu et al [16]. Subsequent studies detected the expression of CASC2 in various types of cancer and found it to be downregulated in cancer tissues as compared with para-cancer or normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA cancer susceptibility candidate 2 (CASC2), located at chromosome 10q26, has been identified as a novel lncRNA that was first found to be downregulated in endometrial cancer [16]. Now increasing numbers of studies have shown that CASC2 is also significantly downregulated in other cancers, such as hepatocellular carcinoma, colorectal cancer, and bladder cancer [17-19], and it could act as a tumor suppressor with implications for diagnosis and therapy [20].…”
Section: Introductionmentioning
confidence: 99%
“…16 CASC2 was found to have heterozygosity loss in endometrial carcinoma and differential expression between normal and tumor tissue. 17 hCV11290602 and rs1369 are located in CASC2 intron 1 and 3 0 -UTR, respectively. rs1369, with genotypes distributed independently from those of rs1797, showed a border-line tendency to have higher proportion of heterozygotes among obese men in a subsample (OR ¼ 1.56, 95% CI: 1.00-2.39, 1 df, P ¼ 0.057).…”
Section: Discussionmentioning
confidence: 99%